Mathematical modeling of drug delivery from one-layer and two-layer torus-shaped devices with external mass transfer resistance - Helbling, Ignacio Marcelo (2011)
A mathematical modeling of controlled release of drug from one-layer and two-layer torus-shaped devices with external mass transfer resistance is presented. Analytical solutions based on the pseudosteady state approximation are derived. The validity of the equations is established in two stages. In the first stage, the validity of the models derived for more complex systems is determined by comparison with profiles predicted by the simplest model, in asymptotic cases. In the second stage, the reliability and usefulness of the models are ascertained by comparison of the simulation results with vaginal rings experimental release data reported in the literature. In order to measures quantitatively the fit of the theoretical models to the experimental data, the pair-wise procedure is used. A good agreement between the prediction of the models and the experimental data is observed. The models are applicable only to torusshaped systems in where the initial load of drug is higher than its solubility in the polymer.